2013
DOI: 10.1017/s1074070800004685
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Research: Implications for Agricultural and Applied Economists

Abstract: We detail the rewards and barriers to participating in multidisciplinary research (MDR) using a 2011 survey of applied economists at U.S. universities. We compare these findings with an earlier 1993 survey to assess if rewards and barriers have changed over time. Different administrative levels of U.S. universities are sending contradictory signals regarding rewards from MDR. External funding agencies convey positive signals. Although the scope and breadth of questions addressed by applied economists are chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Various researchers have recognized the institutional difficulties and challenges in integrating new systems of thought within an established discipline (e.g., Bammer, 2017;Brandstädter and Sonntag, 2016;Clark and Wallace, 2015;Jacob, 2015;Maxwell and Benneworth, 2018;Mooney et al, 2013). To overcome such challenges, various ID scholars contend that communication is central to the integration of insights from different disciplines (e.g., Brandstädter and Sonntag, 2016;Maxwell and Benneworth, 2018;Menken and Keestra, 2016;Repko and Szostak, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various researchers have recognized the institutional difficulties and challenges in integrating new systems of thought within an established discipline (e.g., Bammer, 2017;Brandstädter and Sonntag, 2016;Clark and Wallace, 2015;Jacob, 2015;Maxwell and Benneworth, 2018;Mooney et al, 2013). To overcome such challenges, various ID scholars contend that communication is central to the integration of insights from different disciplines (e.g., Brandstädter and Sonntag, 2016;Maxwell and Benneworth, 2018;Menken and Keestra, 2016;Repko and Szostak, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that economic disciplines tend to exhibit a selfreferential bias that is skeptical of contributions made by other social science disciplines (Pieters and Baumgartner, 2002). This COMMENT PALGRAVE COMMUNICATIONS | https://doi.org/10.1057/s41599-019-0235-8 appears to be supported in agricultural economics settings where disciplinary activities that promote the use of economics are given greater priority over other subject areas (e.g., Hilmer and Hilmer, 2005;Mooney et al, 2013), such as agribusiness (Detre et al, 2011). As a result, the task of the "gatekeeper" is not only to advocate the merits of a department's peripheral discipline to its economic core, but also to resolve and integrate their inconsistencies.…”
Section: Conceptual Developmentsmentioning
confidence: 92%
See 3 more Smart Citations